Effect of vernalizing temperature on the level of plant hormones in embryos of germinating grains of winter and spring wheat - M. Michniewicz; B. Rożej; A. Chromiński; Z. Chromiński (Acta Societatis Botanicorum Poloniae, 2015)
In embryos of grains of winter and spring wheat germinating at temperature of 1.8—2.0°C the levels of auxins, gibberellins, cytokinins and abscisic acid-like inhibitor were determined. The analyses were performed after 5, 10, 20, 40 and 60 days of chilling. The levels of these hormones were also determined in embryos of grains germinated at 22°C being in the same growth stage as embryos taken from chilled grains. It was stated, that during the germination at vernalizing temperature the level of auxins, GAs and cytokinins increased in embryos of both varietes. The level of these hormones in winter wheat was however higher. The amount of growth inhibitor increased at the beginning of germination in embryos of both wheats and afterwards decreased. It was concluded that the above mentioned changes in the level of auxins, cytokinins and ABA had no direct relation to the process of vernalization. However, the changes in the levels of gibberellins found in embryos of winter wheat during the thermoinduction may be directly connected with the vernalization process.